Aluminum alloy material for extrusion casting and preparation method thereof

By adding titanium powder, boron powder and nano alumina powder to the aluminum alloy, and using extrusion casting technology and electromagnetic stirring technology to generate AlB2 and TiB2, the insufficient performance of existing piston materials under high temperature and high pressure conditions was solved, and the problem of insufficient performance of existing piston materials under high temperature and high pressure conditions was obtained. High-performance aluminum alloy material, suitable for piston applications under high temperature and high speed conditions, and reduces preparation costs.

CN119242996APending Publication Date: 2025-01-03HUNAN JIANGBIN MASCH GRP CORP LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411385122.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing diesel engine piston materials show insufficient heat resistance, fatigue resistance and wear resistance under high temperature and high pressure conditions, and traditional materials are costly and difficult to process, making it difficult to meet high performance needs.

Method used

The aluminum alloy material is prepared by extrusion casting process. By adding titanium powder, boron powder and nano-alumina powder to the aluminum alloy, the nano-alumina powder is uniformly distributed by electromagnetic stirring to produce AlB2 and TiB2, and the aluminum oxide particles are enhanced. The interface bonding ability with aluminum matrix improves the mechanical properties and wear resistance of the material.

Benefits of technology

Aluminum alloy material with excellent mechanical properties, high elastic modulus and high wear resistance is obtained. It is suitable for piston applications under high temperature and high speed conditions, reducing the production cost and improving the overall performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005070815370000101
    Figure BDA0005070815370000101
  • Figure BDA0005070815370000111
    Figure BDA0005070815370000111
  • Figure BDA0005070815370000131
    Figure BDA0005070815370000131
Patent Text Reader

Abstract

The invention provides an aluminum alloy material for extrusion casting, which comprises the following components in percentage by weight: 6.5 to 11.5 percent of Si, 2.1 to 3.7 percent of Ni, 1.2 to 2.3 percent of Cu, 0.4 to 0.8 percent of Mg, 0.08 to 0.15 percent of Zr, B, Ti, Al2O3 and the balance of Al. The invention further provides a preparation method of the aluminum alloy material for extrusion casting. In the process of preparing the aluminum alloy material, mixed powder of titanium powder, boron powder and nanometer aluminum oxide powder is added into an aluminum alloy melt, the mixed powder is uniformly dispersed and distributed in an aluminum matrix under electromagnetic stirring, and the defect sensitivity of aluminum oxide particles to a matrix alloy is reduced through in-situ self-generated AlB2 and TiB2 in combination with an extrusion casting mode; and the interface bonding capacity of the aluminum oxide particles and the aluminum matrix is effectively enhanced, so that the aluminum alloy material with excellent mechanical property, high elastic modulus and high wear resistance is obtained, and the use requirements of the high-performance piston under the conditions of high temperature and high rotating speed can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aluminum alloys, and in particular to an aluminum alloy material for extrusion casting and a preparation method thereof. Background Art

[0002] The piston is one of the most important parts in the engine and is known as the "heart" of the engine. The piston bears the gas pressure and transmits energy to the connecting rod through the piston pin to drive the crankshaft movement. Therefore, the design of the piston is an important factor in determining the overall quality of the engine. At present, with the continuous improvement of technical indicators such as diesel engine power and explosion pressure, the working environment of the piston has become quite harsh, and it is subjected to high pressure, high speed, high temperature mechanical load and thermal load. The piston in this working environment has special requirements for its material. The piston material must have the characteristics of low density, light weight, good thermal conductivity, poor heat absorption, and small thermal expansion coefficient, and have sufficient high temperature strength, wear resistance and corrosion resistance, and good dimensional stability; in addition, it should also have the characteristics of good forming and processing performance and low cost.

[0003] At present, diesel engine pistons at home and abroad are formed by gravity casting, and most of their piston materials are eutectic Al-Si alloys. The representative Al-Si alloy piston material grade is ZL109 (the composition is shown in Table 1). In order to further improve the heat resistance of ZL109 piston material, the composition of ZL109 is optimized, the content of strengthening elements such as Cu and Ni is increased, and the piston alloy AlSiCuMgNi material is improved (the composition is shown in Table 2).

[0004] Table 1 Composition data of ZL109 material (wt%)

[0005] Si Cu Mg Ni Fe Al 11~13 0.5~1.5 0.4~0.6 0.8~1.5 ≤0.5 margin

[0006] Table 2 Composition data of AlSiCuMgNi materials (wt%)

[0007] Si Cu Mg Ni Fe Al 11~13 3.5~5 0.6~1.2 1.5~3 ≤0.5 margin

[0008] With the development of science and technology, the lightweight, high mobility and high reliability of vehicles have put forward higher requirements for diesel engine high power and high explosion pressure. The piston will work under higher temperature and higher friction and wear conditions, and bear higher thermal and mechanical loads. Traditional piston materials can no longer meet the high-tech index requirements of diesel engines, so the development of high-performance piston materials is an inevitable trend.

[0009] The main disadvantages of ZL109 piston material and AlSiCuMgNi piston material are that the above piston materials cannot withstand operating temperatures of 400°C and above, and fatigue cracks are very likely to occur in the piston. At the same time, the piston cannot guarantee reliability under high speed conditions, that is, the above piston materials are insufficient in heat resistance, high strength, high fatigue resistance, high wear resistance and other properties.

[0010] In order to improve the performance of piston materials, domestic and foreign piston companies have successively applied Al2O3 fibers to pistons, with AlSiCuMgNi as the base material. As a result, the wear resistance, dimensional stability, high-temperature strength, etc. of the piston have been improved to a certain extent. However, Al2O3 fibers will cause the piston material to become anisotropic, and there are also problems such as difficulty in combining with aluminum liquid, difficulty in mechanical processing, and high preparation cost. Therefore, the above-mentioned piston material has not been able to be applied in large quantities. Summary of the invention

[0011] The technical problem solved by the present invention is to provide an aluminum alloy material for extrusion casting and a preparation method thereof. The aluminum alloy material for extrusion casting provided by the present application has excellent mechanical properties, high elastic modulus and high wear resistance.

[0012] In view of this, the present application provides an aluminum alloy material for extrusion casting, which comprises, by mass percentage:

[0013] Si6.5~11.5%, Ni 2.1~3.7%, Cu1.2~2.3%, Mg 0.4~0.8%, Zr0.08~0.15%, Sr 0.015~0.035%, Fe≤0.7%, also including B, Ti, Al2O3 and the balance of Al;

[0014] The contents of B, Ti and Al2O3 are x, y and z respectively, wherein x is 0.15-0.3%, y is 0.02-0.06%, and the following relationship is satisfied: 9.5x+1.7y+0.1≤z≤13x+2.1y+0.4.

[0015] Preferably, z=1.6-4.2%.

[0016] The present application also provides a method for preparing the aluminum alloy material, comprising the following steps:

[0017] S1) mixing titanium powder, boron powder and nano-alumina powder, and drying to obtain a mixed powder;

[0018] S2) mixing silicon raw material, copper raw material, nickel raw material, aluminum raw material and zirconium raw material according to a certain proportion, melting them and then adding the mixed powder to obtain an alloy melt;

[0019] S3) degassing the alloy melt and adding magnesium raw material and aluminum strontium alloy, and then refining;

[0020] S4) slagging the refined alloy melt to obtain molten aluminum;

[0021] S5) electromagnetically stirring the molten aluminum, and then performing extrusion casting to obtain an aluminum alloy material for extrusion casting.

[0022] Preferably, the extrusion casting further comprises:

[0023] The obtained aluminum alloy material is first subjected to a solution treatment and then to an aging treatment;

[0024] The temperature of the solution treatment process is 500-600°C, the time is 5-10 hours, and the cooling medium is 75-100°C hot water;

[0025] The temperature of the aging process is 200-300° C., the time is 8-10 hours, and the cooling medium is air.

[0026] Preferably, in step S1), the mixing adopts a corundum ceramic jar rotary powder mixing, silicon carbide ceramic balls are added to the mixing, and the ratio of the mass of the silicon carbide ceramic balls to the total mass of the titanium powder, the boron powder and the nano-silicon oxide powder is (0.7-2.2):1; the rotation speed of the corundum ceramic jar is 100-150r / min, and the mixing time is 8-10h; the drying temperature is 120-160°C, and the time is 4-10h.

[0027] Preferably, in step S2), the order of ingredients is: silicon raw material, part of aluminum raw material, nickel raw material, copper raw material and aluminum-zirconium alloy;

[0028] During the melting process, another portion of aluminum raw material is added while maintaining the temperature at 400-500° C. for 30-60 minutes;

[0029] The mixing powder is added when the melt temperature is 700-750°C;

[0030] After the mixed powder is added, the temperature of the melt is raised to 800-880° C. and kept warm for 1-2 hours.

[0031] Preferably, the degassing starting temperature is 750-780°C, the degassing rotor speed is 380-460r / min; the refining time is 8-15min, and the argon flow rate is 0.4-0.6m 3 / h.

[0032] Preferably, the amount of the slag-removing agent added is 0.5-1.5% of the total weight of the alloy melt.

[0033] Preferably, the temperature of the electromagnetic stirring is 650-690° C., the time of the electromagnetic stirring is 15-30 min, the stirring frequency is 2.5-3.5 Hz, the stirring intensity is 40%-60%, and the forward and reverse reversal time is 25-35 s / time; the surface flow velocity of the molten aluminum during the electromagnetic stirring is 0.4-1.0 m / s, and the bottom flow velocity is 0.7-1.5 m / s.

[0034] Preferably, the pressure of the extrusion casting is 300-600 bar, the holding time is 10-20 seconds, the mold temperature of the extrusion casting is 150-250°C, and the pouring temperature of the molten aluminum for the extrusion casting is 600-750°C.

[0035] The present application provides a method for preparing an aluminum alloy material for extrusion casting, which comprises firstly mixing titanium powder, boron powder and nano-alumina powder, and obtaining a mixed powder after drying; then melting various raw materials according to a proportion and adding the mixed powder to obtain an alloy melt; then degassing is performed and magnesium raw material and aluminum strontium alloy are added for refining; after refining, slagging is performed to obtain aluminum liquid, and the aluminum liquid is subjected to electromagnetic stirring and then extrusion casting is performed to obtain an aluminum alloy material for extrusion casting; in the process of preparing the aluminum alloy material, the present application directly adds a mixed powder of titanium powder, boron powder and nano-alumina powder to the molten aluminum liquid, and utilizes electromagnetic stirring to make the nano-alumina powder uniformly dispersed in the aluminum matrix, and in combination with the extrusion casting process, the in-situ self-generated AlB2 and TiB2 reduce the defect sensitivity of the aluminum oxide particles to the matrix alloy, and at the same time effectively enhance the interface bonding ability of the aluminum oxide particles and the aluminum matrix under the extrusion action, thereby obtaining an aluminum alloy material with excellent mechanical properties, high elastic modulus and high wear resistance; the aluminum alloy material can be used to prepare pistons to meet the use requirements of high-performance pistons under high temperature and high speed conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a metallographic structure photograph (100×) of the aluminum alloy material prepared in Example 1 of the present invention;

[0037] Figure 2 This is a microstructure photograph (200×) of the aluminum alloy material prepared in Example 1 of the present invention;

[0038] Figure 3 This is a microstructure photograph (500×) of the aluminum alloy material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0039] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.

[0040] In view of the performance requirements of aluminum alloy materials for pistons in the prior art for mechanical properties, high elastic modulus and high wear resistance, the present application provides an aluminum alloy material and a preparation method thereof. The present application directly adds Ti powder, B powder and Al2O3 powder to the aluminum alloy material, and uses the mixed powder addition of the three to obtain better performance than a single reinforcement body reinforced aluminum alloy matrix through the coupling effect between phase interfaces and between phases. While maintaining the advantages of each raw material, excellent comprehensive performance is obtained through the mutual synergy between multiple components. Specifically, the embodiment of the present invention discloses an aluminum alloy material for extrusion casting, which, in terms of mass percentage, includes:

[0041] Si6.5~11.5%, Ni 2.1~3.7%, Cu1.2~2.3%, Mg 0.4~0.8%, Zr0.08~0.15%, Sr 0.015~0.035%, Fe≤0.7%, also including B, Ti, Al2O3 and the balance of Al;

[0042] The contents of B, Ti and Al2O3 are x, y and z respectively, wherein x is 0.15-0.3%, y is 0.02-0.06%, and the following relationship is satisfied: 9.5x+1.7y+0.1≤z≤13x+2.1y+0.4.

[0043] In the aluminum alloy material provided in the present application, Ti, B and Al2O3 are additionally added to the aluminum alloy matrix as mixed materials. In the matrix alloy, the content of Si is 6.5-11.5%, specifically, the content of Si is 6.8-11.2%, and more specifically, the content of Si is 7.3-9.3%. For example, the content of Si in the present application is 6.6%, 6.7%, 6.9%, 7.0%, 7.1%, 7.1%, 7.2%, 7.4%, 7.5%, 7.6%, 7.7%, 7.8%, 7.9 %, 8.0%, 8.1%, 8.2%, 8.3%, 8.4%, 8.5%, 8.6%, 8.7%, 8.8%, 8.9%, 9.0%, 9.1%, 9.2%, 9.4%, 9.5%, 9.6%, 9.7%, 9.8%, 9.9%, 10.0%, 10.1%, 10.2%, 10.3%, 10.4%, 10.5%, 10.6%, 10.7%, 10.8%, 10.9%, 11.0%, 11.1%, 11.3%, 11.4%.

[0044] The Ni content is 2.1-3.7%, specifically, the Ni content is 2.5-3.5%, more specifically, the Ni content is 2.8-3.2%; by way of example, the Ni content in this application is 2.2%, 2.3%, 2.4%, 2.6%, 2.7%, 2.9%, 3.0%, 3.1%, 3.3%, and 3.4%.

[0045] The Cu content is 1.2-2.3%, specifically, the Cu content is 1.5-2.2%, more specifically, the Cu content is 1.6-1.9%; for example, the Cu content in this application is 1.3%, 1.4%, 1.6%, 1.7%, 1.8%, 2.0%, and 2.1%.

[0046] The content of Mg is 0.4-0.8%; for example, the content of Mg in the present application is 0.5%, 0.6%, and 0.7%.

[0047] The content of Zr is 0.08% to 0.15%; for example, the content of Zr in this application is 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, and 0.14%.

[0048] The Sr content is 0.015-0.035%, specifically, the Sr content is 0.019-0.031%, more specifically, the Sr content is 0.022-0.028%; for example, the Sr content in the present application is 0.016%, 0.017%, 0.018%, 0.020%, 0.021%, 0.023%, 0.024%, 0.025%, 0.026%, 0.027%, 0.029%, 0.030%, 0.032%, 0.033%, and 0.034%.

[0049] Fe≤0.7%, specifically, the content of Fe is 0.25-0.68%, more specifically, the content of Fe is 0.37-0.54%; for example, the content of Fe in the present application is 0.26%, 0.27%, 0.28%, 0.29%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.58%, 0.61%, 0.63%, 0.66%, 0.69%.

[0050] The content of B is 0.15-0.3%, specifically, the content of B is 0.16-0.28%, more specifically, the content of B is 0.20-0.26%; for example, the content of B in this application is 0.16%, 0.17%, 0.18%, 0.19%, 0.21%, 0.22%, 0.23%, 0.24%, 0.26%, 0.27%, 0.28%, and 0.29%.

[0051] The content of Ti is 0.02% to 0.06%. For example, the content of Ti is 0.03%, 0.04%, 0.05%, and 0.06%.

[0052] The content of Al2O3 is limited by the content of B and Ti, and the content relationship of the three satisfies: 9.5x+1.7y+0.1≤z≤13x+2.1y+0.4; specifically, the content of Al2O3 is 1.6-4.2%, more specifically, the content of Al2O3 is 2.1-3.7%, more specifically, the content of Al2O3 is 2.6-3.5%; by way of example, the content of Al2O3 in the present application is 1.7%, 1.8%, 1.9%, 2.0%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.8%, 3.9%, 4.0%, 4.1%.

[0053] The present application also provides a method for preparing an aluminum alloy material, comprising the following steps:

[0054] S1) mixing titanium powder, boron powder and nano-alumina powder, and baking to obtain mixed powder;

[0055] S2) mixing silicon raw material, copper raw material, nickel raw material, aluminum raw material and zirconium raw material according to a certain proportion, melting them and then adding the mixed powder to obtain an alloy melt;

[0056] S3) degassing the alloy melt and adding magnesium raw material and aluminum strontium alloy, and then refining;

[0057] S4) slagging the refined alloy melt to obtain molten aluminum;

[0058] S5) electromagnetically stirring the molten aluminum, and then performing extrusion casting to obtain an aluminum alloy material for extrusion casting.

[0059] In the process of preparing aluminum alloy materials, titanium powder, boron powder and nano-alumina powder are first mixed and dried to obtain a mixed powder; in this process, the particle size of the titanium powder is preferably 50-125μm, the particle size of the boron powder is preferably 50-90nm, and the particle size of the nano-alumina powder is 1-50μm. In order to make the titanium powder, boron powder and nano-alumina powder evenly distributed in the aluminum alloy matrix, the titanium powder, boron powder and nano-alumina powder need to be mixed first; in the present application, it is preferred to use a corundum ceramic jar rotary powder mixing method to obtain a uniformly mixed powder by diffusion mixing, and silicon carbide ceramic balls are added during the mixing process. The ratio of the mass of the silicon carbide ceramic balls to the total mass of the titanium powder, boron powder and the nano-silicon oxide powder is (0.7-2.2):1. Specifically, the mass of the silicon carbide ceramic balls and the mass of the titanium powder, The total mass ratio of the boron powder to the nano silicon oxide powder is 1:1; the rotation speed of the corundum ceramic jar is 100-150r / min, and the mixing time is 8-10h, specifically, the rotation speed of the corundum ceramic jar is 100-120r / min; the drying temperature is 120-160°C, and the time is 4-10h; specifically, the drying temperature is 125-156°C, and the time is 4.5-8.5h; more specifically, the drying temperature is 130-140°C, and the time is 5-7h.

[0060] According to the present invention, the material is then charged and melted, that is, silicon raw material, copper raw material, nickel raw material, aluminum raw material and zirconium raw material are mixed in proportion, melted and then added with the mixed powder to obtain an alloy melt; in this process, the silicon raw material can be selected from crystalline silicon, the copper raw material can be selected from cathode copper, the nickel raw material can be selected from nickel plate, the zirconium raw material can be selected from aluminum zirconium alloy, and the aluminum raw material is selected from pure aluminum ingots. At this time, it is preferred to add part of the pure aluminum ingots. After the above raw materials are charged into the furnace according to the ingredients, the temperature is slowly increased to 400-500°C and kept warm for 30-60 minutes before adding the remaining aluminum ingots. When the temperature rises to 700-750°C, the mixed powder is added. More specifically, the timing of adding the mixed powder is 700-720°C. After adding the mixed powder, keep warm for 30-40 minutes and stir continuously during the period, at least 5 times; when the melt is heated to 805-872°C, keep warm for 1-2 hours, and stir the slag for at least 2 minutes to remove the surface scum.

[0061] The present application then degasses and refines the alloy melt obtained above; specifically, the degassing is started when the temperature of the alloy melt is reduced to 750-780°C, the alloy melt is stirred, and magnesium ingots and aluminum strontium alloy are added at the same time; the rotor speed of the degassing is 380-460r / min, specifically, the rotor speed is 390-420r / min. The refining time is 8-15min, and the argon flow rate is 0.4-0.6m 3 / h; Specifically, the refining time is 10 to 14 minutes, and the argon flow rate is 0.45 to 0.55 m 3 / h.

[0062] After refining, slag removal is performed according to the separation of the aluminum slag after refining, specifically: adding a slag removal agent to the surface of each furnace of aluminum liquid, and turning the slag on the liquid surface for at least 2 minutes, and then cleaning the slag on the surface of the aluminum liquid; the amount of the slag removal agent added for slag removal is 0.5-1.5% of the total weight of the alloy melt, specifically, the amount of the slag removal agent added is 0.8-1.2% of the total weight of the alloy melt.

[0063] The present application then carries out electromagnetic stirring of the refined aluminum liquid, and the electromagnetic stirring is specifically carried out in the machine-side furnace of the electromagnetic induction effect of the extrusion equipment, and the temperature is maintained at 650-690°C, specifically, the temperature is maintained at 660-680°C. In the operation of electromagnetic stirring, the electromagnetic stirring time is 15-30min, the stirring frequency is 2.5-3.5Hz, the stirring intensity is 40%-60%, and the forward and reverse reversing time is 25-35s / time; the surface flow velocity of the aluminum liquid of the electromagnetic stirring is 0.4-1.0m / s, and the bottom flow velocity is 0.7-1.5m / s; specifically, the electromagnetic stirring time is 19-27min, the stirring frequency is 2.8-3.2Hz, the stirring intensity is 50%, and the forward and reverse reversing time is 28-32s / time; the surface flow velocity of the aluminum liquid of the electromagnetic stirring is 0.45-0.9m / s, and the bottom flow velocity is 0.74-1.3m / s.

[0064] The present application finally performs extrusion casting on the aluminum liquid after electromagnetic stirring to obtain an aluminum alloy material for extrusion casting; the extrusion casting includes mold preparation, debugging and mold heating, spraying of mold release agent, liquid lifting, low-speed and high-pressure filling, pressurization and pressure maintenance, and mold opening and taking out. In the mold preparation step, check the status of the fixed mold and the movable mold of the die-casting mold, check the water flow of the inner mold, and do not allow water blockage, small water flow or uncontrolled long water flow, and do not allow leakage / dripping at the inner mold pipe joint. In the debugging and mold heating steps, the extrusion casting mold is heated to 150-250°C, and the liquid riser is heated to 680-710°C. In the step of spraying the mold release agent, the extrusion casting mold is sprayed with the mold release agent, and the coating is thicker in the area close to the riser and the thin-walled area, and thinner in the area away from the riser and the wide and thick part of the casting; the mold release agent is a mold release agent well known to those skilled in the art, and this application does not impose any special restrictions on this. In the step of raising the liquid, the aluminum liquid in the machine-side furnace reaches 600-750℃, and the machine-side furnace is pressurized. The aluminum liquid in the machine-side furnace is transported to the barrel pressure chamber by air pressure. In the step of low-speed and high-pressure filling, the punch moves upward, and the aluminum liquid is charged into the closed cavity by low-speed and high-pressure. After the filling is completed, the pressure is increased and maintained to prevent gas from mixing into the aluminum liquid, while ensuring that a dense extrusion casting blank is obtained. Finally, the movable mold and the fixed mold are separated to take out the piston blank. In the above-mentioned extrusion casting step, the pressure of the extrusion casting is 300-600 bar, the holding time is 10-20 s, the mold temperature of the extrusion casting is 150-250°C, and the pouring temperature of the molten aluminum for extrusion casting is 600-750°C; specifically, the pressure of the extrusion casting is 300-550 bar, the holding time is 12-18 s, the mold temperature of the extrusion casting is 180-220°C, and the pouring temperature of the molten aluminum for extrusion casting is 640-710°C; more specifically, the pressure of the extrusion casting is 342-460 bar, the holding time is 13-15 s, the mold temperature of the extrusion casting is 190-200°C, and the pouring temperature of the molten aluminum for extrusion casting is 645-685°C.

[0065] According to the present invention, after obtaining the above-mentioned blank, it is also heat treated, and the heat treatment process includes a solution treatment process and an aging process performed in sequence; the temperature of the solution treatment process is 500-600°C, the time is 5-10h, and the cooling medium is 75-100°C hot water; the temperature of the aging process is 200-300°C, the time is 8-10h, and the cooling medium is air; specifically, the temperature of the solution treatment process is 525-545°C, the time is 6-8h; the temperature of the aging process is 205-275°C, and the time is 8-10h; more specifically, the temperature of the solution treatment process is 530-540°C, the time is 7-8h; the temperature of the aging process is 215-225°C, and the time is 9-10h.

[0066] The present invention provides a method for preparing an aluminum alloy material for extrusion casting, wherein titanium powder, boron powder and nano-alumina powder are additionally added to the alloy matrix, and the alumina powder is an ultrafine nano-alumina powder with a size of 1 to 50 μm, which has good chemical compatibility with the aluminum alloy matrix and almost no interface chemical reaction occurs; the high-performance alumina ceramic particles in the present invention can greatly improve the modulus and strength of the aluminum alloy, but will restrict the deformation ability of the matrix alloy in the matrix alloy, so that the rheological stress of the matrix alloy increases during the deformation process, thereby causing the alloy material to be highly sensitive to defects, and this effect increases with the increase of the ceramic reinforcement content. Therefore, the present invention adds a certain proportion of light and high modulus boron powder (boron atoms have a layered structure similar to graphite) and alumina powder for mixed powder treatment, and the B powder reacts in the aluminum alloy melt to generate a small amount of AlB2 and a trace amount of TiB2; reaction equation 1: (2B+Al→AlB2); at the same time, the Ti element generates Al3Ti in the aluminum alloy, reaction equation 2: (AlB2+Al3Ti→TiB2+4Al). Since Al2O3 metal has a high melting point and is an added powder particle, it is difficult to control the uniform distribution of Al2O3 reinforcement in the matrix, the aluminum alloy melt has poor wettability on the surface of the Al2O3 reinforcement, and the interface characterization and control at high temperature become very difficult. AlB2 and TiB2 are both similar to the layered structure of boron atoms, so the wettability and compatibility between the in-situ self-generated AlB2 and TiB2 phases and the aluminum matrix are very excellent, which can optimize the interface bonding between the Al2O3 reinforcement particles and the aluminum matrix, improve the wettability, and well supplement the damage tolerance of the Al2O3 / Al composite material, effectively improve the strength and plasticity of the composite material, and reduce the defect sensitivity of the alumina powder to the matrix alloy; at the same time, the present invention adopts extrusion casting to effectively enhance the interface bonding ability of the alumina reinforcement and the alloy bonding strength under boost pressure, and prepares an aluminum alloy material with excellent tensile properties, high elastic modulus and wear resistance, which can be used to prepare piston materials.

[0067] In summary, the present invention utilizes a mixed powder process of titanium powder, boron powder and nano-alumina reinforcement powder to obtain better performance than a single reinforcement reinforced composite material through the coupling effect between phase interfaces and between phases; while maintaining the advantages of each component material, excellent comprehensive performance is obtained through the mutual synergy between multiple components, which not only reduces costs but also improves the practicability of the material.

[0068] In order to further understand the present invention, the aluminum alloy material for extrusion casting and the preparation method thereof provided by the present invention are described in detail below in conjunction with embodiments. The protection scope of the present invention is not limited by the following embodiments.

[0069] Table 3 Alloy raw material selection table for pre-melting materials

[0070]

[0071]

[0072] Example 1

[0073] (1) Ingredients

[0074] Add various raw materials according to the raw material selection table described in Table 3, and mix the ingredients according to the proportions in the ingredient table described in Table 7;

[0075] (2) Powder pretreatment

[0076] In order to make titanium powder, boron powder and ultrafine nano-alumina powder evenly distributed in the composite material, the powder needs to be mixed before the product is prepared by the squeeze casting process; the corundum ceramic tank rotary powder mixing method is used to mix titanium powder, boron powder and ultrafine nano-alumina powder according to the ratio relationship in Table 7 by diffusion mixing to obtain a uniformly mixed powder, silicon carbide ceramic balls are added during the mixing process, the mass ratio of the balls to the powder is about 1:1, the tank speed is 105r / min, the mixing time is 8h, and then the baking temperature is 130℃, the baking time is 5h, and the mixed powder is obtained;

[0077] (3) Charge melting

[0078] The order of charging the pre-melted alloy of aluminum alloy materials is: all crystalline silicon → part of pure aluminum ingots, nickel plates, cathode copper and aluminum-zirconium alloys, and try to make each added material compact without leaving obvious gaps; after charging the melting furnace, the temperature should be slowly raised, and after keeping it at 500℃ for 35 minutes, the remaining aluminum ingots should be added during the melting process. When the temperature rises to 700℃, add the above mixed powder, and then put in a thermocouple for temperature monitoring, keep it warm for 30 minutes, stir it with a stirring rod for at least 5 times, and when the aluminum liquid temperature rises to 815℃, keep it warm for 1.2 hours to allow it to fully react, and use a slag scoop to turn over the slag on the liquid surface for at least 2 minutes, and then remove the surface slag;

[0079] (4) Rotary degassing

[0080] The alloy melt in step (3) is taken out of the furnace, the temperature is lowered to 760°C, and the degasser is turned on to perform rotary degassing on the alloy melt. At the same time, magnesium ingots and aluminum-strontium alloy are added. After degassing, the rotor rises, and the air holes of the rotor are immediately cleared with a tool. The slag on the liquid surface is turned over with a slag scoop, and then the slag on the surface of the aluminum liquid is cleaned; the rotor and the baffle automatically sink, and the refining stage is automatically entered; rotary degassing parameters: rotor speed 410r / min, refining time 9min, compressed air flow rate 0.46m 3 / h;

[0081] (5) Slag removal

[0082] According to the separation of aluminum slag after refining, 0.6% of the total mass of slag remover can be added to the surface of each furnace of aluminum liquid, and the slag on the liquid surface can be turned over with a slag scoop for at least 2 minutes, and then the floating slag on the surface of the aluminum liquid can be cleaned up, and the scooped slag can be poured onto the slag frying platform or slag frying bucket, and the slag can be scattered as much as possible;

[0083] (6) Pour the molten aluminum into the furnace beside the extrusion equipment for electromagnetic stirring

[0084] Pour the molten aluminum after slag removal into the electromagnetic induction furnace of the extrusion equipment, keep the temperature at 660℃, turn on the electromagnetic stirring, and set the stirring process parameters: stirring time: 20min, stirring frequency: 2.7Hz, stirring intensity: 50%, forward and reverse reversing time: 27s / time, the surface flow velocity of the aluminum melt is 0.45-0.55m / s, and the bottom flow velocity is 0.74-0.86m / s;

[0085] (7) Extrusion casting

[0086] 1) Mold preparation

[0087] Check the status of the fixed mold and the movable mold, check the water flow of the inner mold, and do not allow the water channel to be blocked, the water flow to be small, or there to be uncontrolled long water flow. Leakage / dripping at the inner mold pipe joint is not allowed;

[0088] 2) Debugging and mold heating

[0089] After the mold is installed, heat the mold to 190℃, adjust the heating temperature of the liquid riser to 685℃, and debug the installed die-casting mold according to the product process parameters;

[0090] 3) Spraying

[0091] Spray the mold release agent on the mold. Because the casting adopts a sequential solidification method, when spraying the mold release agent, it should be noted that the coating should be thicker in the area close to the riser and the thin-walled area, and thinner in the area away from the riser and the wide and thick part of the casting; set the process parameters in the pressure casting process through the control cabinet;

[0092] 4) Liquor rise

[0093] The alloy in the machine-side furnace is melted to a preset temperature of 645°C, the machine-side furnace is pressurized, and a fixed amount of alloy solution in the machine-side furnace is transported to the barrel pressure chamber by air pressure;

[0094] 5) Low speed filling and high pressure

[0095] The punch moves upward to squeeze the alloy liquid into the closed cavity.

[0096] 6) Pressurization and pressure maintenance

[0097] After filling, the pressure is increased and maintained. The pressure is 342 bar and the holding time is 13 seconds to prevent gas from mixing into the metal melt and ensure that a dense squeeze casting blank is obtained.

[0098] 7) Open the mold and take out the parts

[0099] The movable die is separated from the fixed die, and the piston blank is taken out;

[0100] (8) Blank heat treatment process

[0101] The blank obtained above is subjected to solution treatment and aging in sequence according to the heat treatment process in Table 4 to obtain an aluminum alloy material;

[0102] Table 4 Heat treatment process data

[0103]

[0104] Example 2

[0105] (1) Ingredients

[0106] Add various raw materials according to the raw material selection table described in Table 3 above, and mix the ingredients according to the proportions in the ingredient table described in Table 7;

[0107] (2) Powder pretreatment

[0108] In order to make titanium powder, boron powder and ultrafine nano-alumina powder evenly distributed in the composite material, the powder needs to be mixed before the product is prepared by the squeeze casting process; the corundum ceramic tank rotary powder mixing method is used to mix titanium powder, boron powder and ultrafine nano-alumina powder according to the ratio relationship in Table 7 by diffusion mixing to obtain a uniformly mixed powder, silicon carbide ceramic balls are added during the mixing process, the mass ratio of balls to powder is about 1:1, the tank speed is 110r / min, the mixing time is 9h, and then the baking temperature is 136°C, the baking time is 6.5h, and the mixed powder is obtained;

[0109] (3) Charge melting

[0110] The order of charging the pre-melted alloy of aluminum alloy materials is: all crystalline silicon → part of pure aluminum ingots, nickel plates, cathode copper and aluminum-zirconium alloys. Try to make each added material compact without leaving obvious gaps. After charging the melting furnace, the temperature should be slowly raised. After keeping it at 500℃ for 45 minutes, add the remaining aluminum ingots during the melting process. When the temperature rises to 710℃, add the above mixed powder, and then put in a thermocouple for temperature monitoring. Keep it warm for 35 minutes and stir it with a stirring rod for at least 5 times. When the temperature of the aluminum liquid rises to 835℃, keep it warm for 1.5 hours to allow it to react fully. Use a slag scoop to turn over the slag on the liquid surface for at least 2 minutes, and then remove the surface slag.

[0111] (4) Rotary degassing

[0112] The alloy melt in step (3) is taken out of the furnace, the temperature is lowered to 765°C, and the degasser is turned on to perform rotary degassing on the alloy melt. At the same time, magnesium ingots and aluminum-strontium alloy are added. After degassing, the rotor rises, and the air holes of the rotor are immediately cleared with a tool. The slag on the liquid surface is turned over with a slag scoop, and then the slag on the surface of the aluminum liquid is cleaned; the rotor and the baffle automatically sink, and the refining stage is automatically entered; rotary degassing parameters: rotor speed 420r / min, refining time 11min, compressed air flow rate 0.52m 3 / h;

[0113] (5) Slag removal

[0114] According to the separation of aluminum slag after refining, 0.8% of the total mass of slag remover can be added to the surface of each furnace of aluminum liquid, and the slag on the liquid surface can be turned over with a slag scoop for at least 2 minutes, and then the floating slag on the surface of the aluminum liquid can be cleaned up, and the scooped slag can be poured onto the slag frying platform or slag frying bucket, and the slag can be scattered as much as possible;

[0115] (6) Pour the molten aluminum into the furnace beside the extrusion equipment for electromagnetic stirring

[0116] Pour the molten aluminum after slag removal into the electromagnetic induction furnace of the extrusion equipment, keep the temperature at 670℃, turn on the electromagnetic stirring, set the stirring process parameters: stirring time: 22min, stirring frequency: 3Hz, stirring intensity: 50%, forward and reverse reversing time: 30s / time, the surface flow velocity of the aluminum melt is 0.56-0.78m / s, and the bottom flow velocity is 0.87-1.1m / s;

[0117] (7) Extrusion casting

[0118] 1) Mold preparation

[0119] Check the status of the fixed mold and the movable mold, check the water flow of the inner mold, and do not allow the water channel to be blocked, the water flow to be small, or there to be uncontrolled long water flow. Leakage / dripping at the inner mold pipe joint is not allowed;

[0120] 2) Debugging and mold heating

[0121] After the mold is installed, heat the mold to 200℃, adjust the heating temperature of the liquid riser to 695℃, and debug the installed die-casting mold according to the product process parameters;

[0122] 3) Spraying

[0123] Spray the mold release agent on the mold. Because the casting adopts a sequential solidification method, when spraying the mold release agent, it should be noted that the coating should be thicker in the area close to the riser and the thin-walled area, and thinner in the area away from the riser and the wide and thick part of the casting; set the process parameters in the pressure casting process through the control cabinet;

[0124] 4) Liquor rise

[0125] The alloy in the machine-side furnace is melted to a preset temperature of 685°C, the machine-side furnace is pressurized, and a fixed amount of alloy solution in the machine-side furnace is transported to the barrel pressure chamber by air pressure;

[0126] 5) Low speed filling and high pressure

[0127] The punch moves upward to squeeze the alloy liquid into the closed cavity;

[0128] 6) Pressurization and pressure maintenance

[0129] After filling, the pressure is increased and maintained. The pressure is 460 bar and the holding time is 15 seconds to prevent gas from mixing into the metal melt and ensure that a dense extrusion casting blank is obtained.

[0130] 7) Open the mold and take out the parts

[0131] The movable die is separated from the fixed die, and the piston blank is taken out;

[0132] 8) Heat treatment process of blank

[0133] The blank obtained above is subjected to solution treatment and aging in sequence according to the heat treatment process in Table 5 to obtain an aluminum alloy material;

[0134] Table 5 Heat treatment process data

[0135]

[0136] Example 3

[0137] (1) Ingredients

[0138] Add various raw materials according to the raw material selection table described in Table 3 above, and mix the ingredients according to the proportions in the ingredient table described in Table 7;

[0139] (2) Powder pretreatment

[0140] In order to make titanium powder, boron powder and ultrafine nano-alumina powder evenly distributed in the composite material, the powder needs to be mixed before the product is prepared by the squeeze casting process; the corundum ceramic tank rotary powder mixing method is adopted, and the titanium powder, boron powder and ultrafine nano-alumina powder are mixed by diffusion powder mixing according to the ratio relationship in Table 4 to obtain a uniformly mixed powder, and silicon carbide ceramic balls are added during the mixing process, and the mass ratio of the balls to the powder is about 1:1, the tank speed is 120r / min, the mixing time is 10h, and then the baking temperature is 155°C, and the baking time is 8.2h to obtain the mixed powder;

[0141] (3) Charge melting

[0142] The order of charging the pre-melted alloy of aluminum alloy materials is: all crystalline silicon → part of pure aluminum ingots, nickel plates, cathode copper and aluminum-zirconium alloy. Try to make each added material compact without leaving obvious gaps. After charging the melting furnace, the temperature should be slowly raised. After keeping it at 500℃ for 55 minutes, add the remaining aluminum ingots during the melting process. When the temperature rises to 720℃, add the above mixed powder, and then put in a thermocouple for temperature monitoring. Keep it warm for 40 minutes and stir it with a stirring rod for at least 5 times. When the temperature of the aluminum liquid rises to 870℃, keep it warm for 2 hours to allow it to react fully. Use a slag scoop to turn over the slag on the liquid surface for at least 2 minutes, and then remove the surface slag.

[0143] (4) Rotary degassing

[0144] The alloy melt in step (3) is taken out of the furnace, the temperature is lowered to 780°C, and the degasser is turned on to perform rotary degassing on the alloy melt. At the same time, magnesium ingots and aluminum-strontium alloy are added. After degassing, the rotor rises, and the air holes of the rotor are immediately unblocked with a tool. The slag on the liquid surface is turned over with a slag scoop, and then the slag on the surface of the aluminum liquid is cleaned; the rotor and the baffle automatically sink, and the refining stage is automatically entered; rotary degassing parameters: rotor speed 460r / min, refining time 15min, compressed air flow rate 0.6m 3 / h;

[0145] (5) Slag removal

[0146] According to the separation of aluminum slag after refining, 1% of the total mass of slag remover can be added to the surface of each furnace of aluminum liquid, and the slag on the liquid surface can be turned over with a slag scoop for at least 2 minutes, and then the floating slag on the surface of the aluminum liquid can be cleaned up, and the scooped slag can be poured onto the slag frying platform or slag frying bucket, and the slag can be scattered as much as possible;

[0147] (6) Pour the molten aluminum into the furnace beside the extrusion equipment for electromagnetic stirring

[0148] Pour the molten aluminum after slag removal into the electromagnetic induction furnace of the extrusion equipment, keep the temperature at 690℃, turn on the electromagnetic stirring, and set the stirring process parameters: stirring time: 26min, stirring frequency: 3.4Hz, stirring intensity: 50%, forward and reverse reversing time: 35s / time, the surface flow velocity of the molten aluminum is 0.82-0.9m / s, and the bottom flow velocity is 1.1-1.3m / s;

[0149] (7) Extrusion casting

[0150] 1) Mold preparation

[0151] Check the status of the fixed mold and the movable mold, check the water flow of the inner mold, and do not allow the water channel to be blocked, the water flow to be small, or there to be uncontrolled long water flow. Leakage / dripping at the inner mold pipe joint is not allowed;

[0152] 2) Debugging and mold heating

[0153] After the mold is installed, heat the mold to 210℃, adjust the heating temperature of the liquid riser to 710℃, and debug the installed die-casting mold according to the product process parameters;

[0154] 3) Spraying

[0155] Spray the mold release agent on the mold. Because the casting adopts a sequential solidification method, when spraying the mold release agent, it should be noted that the coating should be thicker in the area close to the riser and the thin-walled area, and thinner in the area away from the riser and the wide and thick part of the casting; set the process parameters in the pressure casting process through the control cabinet;

[0156] 4) Liquor rise

[0157] The alloy in the machine-side furnace is melted to a preset temperature of 700°C, the machine-side furnace is pressurized, and a fixed amount of alloy solution in the machine-side furnace is transported to the barrel pressure chamber by air pressure;

[0158] 5) Low speed filling and high pressure

[0159] The punch moves upward to squeeze the alloy liquid into the closed cavity;

[0160] 6) Pressurization and pressure maintenance

[0161] After filling, the pressure is increased and maintained. The pressure is 525 bar and the holding time is 17 seconds to prevent gas from mixing into the metal melt and ensure that a dense squeeze casting blank is obtained.

[0162] 7) Open the mold and take out the parts

[0163] The movable die is separated from the fixed die, and the piston blank is taken out;

[0164] (8) Blank heat treatment process

[0165] The blank obtained above is subjected to solution treatment and aging in sequence according to the heat treatment process in Table 6 to obtain an aluminum alloy material;

[0166] Table 6 Heat treatment process data

[0167]

[0168] Table 7 Composition data of aluminum alloy materials prepared in Examples and Comparative Examples (wt%)

[0169]

[0170]

[0171] The properties of the aluminum alloy materials prepared in the embodiment and the comparative example (the preparation method of the comparative example is the same as that of the embodiment) were tested, and the results are shown in Table 8 and Table 9;

[0172] Table 8 Performance data of aluminum alloy materials prepared in Examples and Comparative Examples

[0173]

[0174]

[0175] Table 9 Linear expansion coefficient (10 -6 m / mK)

[0176]

[0177] Figure 1 to Figure 3 The microstructure photos of the aluminum alloy material prepared in Example 1 at different magnifications are shown in the figure. It can be seen from the figure that the Al2O3 ceramic particles are randomly distributed in three dimensions, and the in-situ self-generated AlB2 and TiB2 phases are evenly distributed around the Al2O3 ceramic particles, optimizing the interface bonding between the Al2O3 reinforcement particles and the aluminum matrix, so that the Al2O3 ceramic particles are evenly distributed in the aluminum matrix. It can be seen that the alumina particles are well bonded to the matrix alloy, without defects such as shrinkage and shrinkage cavities, reducing the defect sensitivity of the alumina powder to the matrix alloy, and effectively improving the strength and plasticity of the Al2O3 / Al composite material.

[0178] The above embodiments are only used to help understand the method and core idea of ​​the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

[0179] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. An aluminum alloy material for extrusion casting, comprising, by mass percentage: Si6.5~11.5%, Ni 2.1~3.7%, Cu1.2~2.3%, Mg 0.4~0.8%, Zr0.08~0.15%, Sr0.015~0.035%, Fe≤0.7%, also including B, Ti, Al2O3 and the balance of Al; The contents of B, Ti and Al2O3 are x, y and z respectively, wherein x is 0.15-0.3%, y is 0.02-0.06%, and the following relationship is satisfied: 9.5x+1.7y+0.1≤z≤13x+2.1y+0.

4.

2. The aluminum alloy material according to claim 1, characterized in that: z=1.6~4.2%。 3. The method for preparing the aluminum alloy material according to claim 1, comprising the following steps: S1) mixing titanium powder, boron powder and nano-alumina powder, and drying to obtain a mixed powder; S2) mixing silicon raw material, copper raw material, nickel raw material, aluminum raw material and zirconium raw material according to a certain proportion, melting them and then adding the mixed powder to obtain an alloy melt; S3) degassing the alloy melt and adding magnesium raw material and aluminum strontium alloy, and then refining; S4) slagging the refined alloy melt to obtain molten aluminum; S5) electromagnetically stirring the molten aluminum, and then performing extrusion casting to obtain an aluminum alloy material for extrusion casting.

4. The preparation method according to claim 3, characterized in that: The extrusion casting further comprises: The obtained aluminum alloy material is first subjected to a solution treatment and then to an aging treatment; The temperature of the solution treatment process is 500-600°C, the time is 5-10 hours, and the cooling medium is 75-100°C hot water; The temperature of the aging process is 200-300° C., the time is 8-10 hours, and the cooling medium is air.

5. The preparation method according to claim 3, characterized in that: In step S1), the mixing adopts a corundum ceramic jar rotary powder mixing, silicon carbide ceramic balls are added to the mixture, and the ratio of the mass of the silicon carbide ceramic balls to the total mass of the titanium powder, the boron powder and the nano silicon oxide powder is (0.7-2.2):1; the rotation speed of the corundum ceramic jar is 100-150r / min, and the mixing time is 8-10h; the drying temperature is 120-160°C, and the time is 4-10h.

6. The preparation method according to claim 3, characterized in that: In step S2), the order of ingredients is: silicon raw material, part of aluminum raw material, nickel raw material, copper raw material and aluminum-zirconium alloy; During the melting process, another portion of aluminum raw material is added while maintaining the temperature at 400-500° C. for 30-60 minutes; The mixing powder is added when the melt temperature is 700-750°C; After the mixed powder is added, the temperature of the melt is raised to 800-880° C. and kept warm for 1-2 hours.

7. The preparation method according to claim 3, characterized in that: The degassing starting temperature is 750-780°C, the degassing rotor speed is 380-460r / min; the refining time is 8-15min, and the argon flow rate is 0.4-0.6m 3 / h.

8. The preparation method according to claim 3, characterized in that: The amount of the slag removing agent added is 0.5-1.5% of the total weight of the alloy melt.

9. The preparation method according to claim 3, characterized in that: The temperature of the electromagnetic stirring is 650-690° C., the time of the electromagnetic stirring is 15-30 min, the stirring frequency is 2.5-3.5 Hz, the stirring intensity is 40%-60%, and the forward and reverse reversal time is 25-35 s / time; the surface flow velocity of the molten aluminum during the electromagnetic stirring is 0.4-1.0 m / s, and the bottom flow velocity is 0.7-1.5 m / s.

10. The preparation method according to claim 3, characterized in that: The pressure of the extrusion casting is 300-600 bar, the holding time is 10-20 seconds, the mold temperature of the extrusion casting is 150-250° C., and the pouring temperature of the molten aluminum for the extrusion casting is 600-750° C.